(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
Synthetic data is an innovative technology in the field of personal data protection and the development of artificial intelligence systems. Starting from a brief overview of the main technical elements of synthetic data, the article delves into its role within the new European digital regulatory framework. Although it is already possible to identify some of the undeniable advantages derived from this technology and the increasing consideration by legislators, there is still a need for further practical developments, and continuous dialogue between relevant stakeholders is encouraged to ensure a fair balance between innovation and the protection of fundamental rights.